Applications of Declarative Programming and Knowledge Management 17th International Conference, INAP 2007, and 21st Workshop on Logic Programming, WLP 2007, W<U+00fc>rzburg, Germany, October 4-6, 2007, Revised Selected Papers - Seipel, Dietmar.; Hanus, Michael.; Wolf, Armin. (Lecture Notes in Computer Science, 2009)
This volume constitutes the thoroughly refereed post-conference proceedings of the 17th International Conference on Applications of Declarative Programming and Knowledge Management, INAP 2007, and the 21st Workshop on Logic Programming, WLP 2007, held in W<U+00fc>rzburg, Germany, during October 4-6, 2007. The 16 thoroughly revised full papers presented together with 1 invited paper were carefully reviewed and selected from numerous submissions. The topics covered are constraints; databases and data mining; extensions of logic programming; and system demonstrations.